Future CO2 emission trends and radical decarbonization path of iron and steel industry in China. (1st December 2021) - Shen, Jialin; Zhang, Qi; Xu, Lisong; Tian, Shuoshuo; Wang, Peng
Abstract: China has set new ambitious national determined contributions (NDC) target to reach the peak of CO2 emissions by 2030, and strive to achieve carbon neutrality by 2060. This urges radical efforts for all industries to neutralize or zeroize their CO2 emission, especially for the iron and steel industry. Here, we establish a comprehensive model to explore the potential CO2 emission pathways of China's iron and steel industry based on NDC and climate target in line with the Paris Agreement. Four scenarios are constructed: business as usual (BAU), NDC, 2-degree, and 1.5-degree. We predict the total CO2 emission from 2015 to 2050 will fall from 1690.82 Mt to 1475.75 Mt, 1249.39 Mt, 484.77 Mt, and 252.13 Mt under those four scenarios, respectively. To achieve 2-degree and 1.5-degree targets, iron and steel industry requires radical decarbonization. To explore the key factors behind the carbon neutrality of steel production, we apply Logarithmic Mean Divisia Index (LMDI) for the 1.5-degree scenario and find that steel production, breakthrough technologies and production structure will become the important factors. To effectively evaluate the CO2 emissions of steel production, we have set up a CO2 emission evaluation indicator system including comprehensive CO2 emission indicator, crude steel CO2 emission indicator, and section CO2 emission indicator. CSC model shows that low discount rates and high carbon prices will make low-carbon technologies cost-beneficial. Accordingly, we further discuss the potential barriers and strategies related to hydrogen steelmaking, carbon capture and storage (CCS), and electricity generation structure revolution to the iron and steel industry. Highlights: China's iron and steel industry needs to accelerate decarbonization under carbon neutrality. A comprehensive model of CO2 emissions in iron and steel industry is established. Steel production, breakthrough technologies and production structure are important ways. Low discount rates and high carbon prices will make technologies cost-beneficial. Many challenges require key strategies to deal with.